Analisis Efektivitas Program Stunting Tahun 2021-2022 di Desa Paya Gambar - Bintang Rizki Angela; Khairunnisa Khairunnisa; Khairil Ihsan; Annisa Bella; Anggi Ramidah Situmorang (Universitas Batanghari Jambi, 2022)
Stunting or short is a chronic malnutrition problem caused by lack of nutritional intake for a long time, resulting in growth disorders in children, namely the child's height is lower or shorter (short) than the standard age. The method used in this research is descriptive quantitative method. This study aims to analyze the success of the program carried out by the Paya Gambar Village Government regarding the Stunting case.Â The Stunting Program in Paya Gambar Village has been effective in reducing stunting cases, which initially numbered 14 people in 2021 to 1 person in 2022. Stunting itself is a health problem that is a priority and cases are handled by the Indonesian government. The Indonesian government has issued Presidential Regulation (PerPres) Number 72 of 2021 concerning the Acceleration of Stunting Reduction. The Indonesian government has targeted to reduce stunting prevalence by 14% in 2024 and a sustainable development target in 2030 based on achievements in 2024.